REPRESENTATION OF THE TEACHINGS AND DOCTRINES OF THE TAREKAT AS A CHARACTER EDUCATION PARADIGM FROM THE PERSPECTIVE OF SUSPECTS - Achmad Faqih; Try Riduwan Santoso; Nurhamzah Nurhamzah (STAI Sebelas April Sumedang, 2026)
The teachings and doctrines of the Tariqa represent the most comprehensive transformative pedagogical system in the Islamic intellectual heritage, yet they have not been fully represented in contemporary character education discourse in a paradigmatic and systematic manner. This study aims to analyze how the teachings and doctrines of the Tariqa can be represented as a holistic paradigm of character education from a Sufi perspective. This research employs a qualitative approach through an integrative literature review method accompanied by hermeneutic analysis of classical Sufi texts and contemporary Islamic education literature. The results reveal three main findings: first, the Sufi maqamat system encompassing taubah, zuhd, sabar, tawakkal, ridha, mahabbah, and ma'rifah represents a gradual, systematic, and continuous character formation roadmap; second, the doctrines of muraqabah and muhasabah function as mechanisms for the continuous internalization of character values by building theo-centric moral awareness more stable than conventional ego-centric approaches; and third, the practices of riyadhah and suhbah constitute transformative pedagogical methods proven effective in forming noble character (akhlaq al-karimah) through habit internalization and exemplary-based learning. This study concludes that the teachings and doctrines of the Tariqa constitute an authentic and transformative paradigm of character education, as they penetrate the qalb dimension of the human soul as the center of moral consciousness a dimension entirely absent in Western character education theories. This study recommends epistemic integration between the Sufi-Tariqa dimension and the contemporary character education framework as a fundamental solution to the moral crisis of the younger generation in Indonesia. Keywords: Representation; Tariqa Teachings; Tariqa Doctrines; Paradigm; Character Education; Tasawuf